Force-velocity profile based training to improve vertical jump performance a systematic review and meta analysis - Paul Solberg; Will G. Hopkins; Vidar Andersen; Kolbjørn Lindberg; Thomas Bjørnsen; Atle Saeterbakken; Gøran Paulsen (Scientific Reports)
Abstract This systematic review and meta-analysis evaluated the effects of training optimized to correct deficits in vertical force–velocity (FV) profiles compared to non-optimized training. Outcomes included changes in the FV profile, vertical jump height, and maximal power. Searches followed PRISMA guidelines and were conducted in PubMed, Web of Science, SPORTDiscus, and Scopus. Study quality was assessed using the PEDro scale. As of March 2025, ten studies were identified; four were eligible for meta-analysis. Individually optimized FV-based training partially corrected a force deficit, fully corrected a velocity deficit, and had little effect on an already optimum FV profile. Effects on maximal power were small to trivial and often unclear when compared with non-optimized training. There were small-moderate improvements in jump height with optimized training, but these gains were comparable to non-optimized training. Heterogeneity was small to moderate, and methodological shortcomings were noted in all studies, including those excluded from the meta-analysis. Overall, it remains unclear if FV-profile-based training outperforms standard approaches. Labeling training “optimized” or “non-optimized” may induce placebo or nocebo effects, underscoring the need for blinded, randomized controlled trials.